A randomized approximation algorithm for computing bucket orders - Ukkonen, Antti; Puolamäki, Kai; Gionis, Aristides; Mannila, Heikki (Information processing letters, 2009)
We show that a simple randomized algorithm has an expected constant factor approximation guarantee for fitting bucket orders to a set of pairwise preferences.